Administrative Capacity in the New EU Member States : The Limits of Innovation? - Verheijen, Tony (Washington, DC: World Bank, 2012)
This study considers key aspects of administrative performance in three areas related to policy, people, and systems. First, in the field of policy, the study addresses issues of performance management, strategic planning and policy coordination and formulation. Second, as regards people, the study reviews human resource management practices such as recruitment and career management, incentive systems and politico-administrative relations with the aim of assessing the extent to which public administrations in the EU8 can attract and retain high quality staff in the context of rapidly changing labor markets. Finally, in relation to systems, the study looks into one specific aspect of public service delivery, namely the extent to which states have introduced e-Governance systems and used these effectively to enhance the business environment. A benchmarking exercise was conducted in each of the key aspects studied. A specific aim of the study was to identify examples of good practice within the region which might be replicable in other EU8 countries. This study reviews the direction of administrative development in the first two years of EU membership in the EU8 and includes a review of general trends in administrative development as well as a benchmarking exercise for a sample of states on selected criteria that illustrate capacity for public management innovations. The study will draw conclusions on ways to address the identified issues and problems in the development of the public management systems of the EU8, with a focus on systems and instruments that would help address the three challenges set out above.